(untitled) (Confluenţe Bibliologice, 2026)
This article examines Putna Monastery, founded by Ștefan the Great, highlighting its historical, cultural, and spiritual significance, its role as a princely necropolis, and the heritage value of its museum collections. The 2024 Romfilatelia stamp issue honoring the monastery and its Byzantine-Romanian traditions is also discussed.